Split application enhances sweetpotato starch production by regulating the conversion of sucrose to starch under reduced nitrogen supply - Du, Xiangbei (Plant physiology and biochemistry : PPB, 2020)
Copyright © 2020 Elsevier Masson SAS. All rights reserved.